Spatial patterns of mesoplastics and coarse microplastics in floodplain soils as resulting from land use and fluvial processes. (December 2020) - Weber, Collin Joel; Opp, Christian
Abstract: Plastic, and especially microplastic, contamination of soils has become a novel research field. After the detection of microplastics in soils, spatial distribution and dynamics are still unknown. However, the potential risks associated with plastic particles in soils cannot be sufficiently assessed without knowledge about the spatial distribution of these anthropogenic materials. Based on a spatial research approach, including soil surveys, this study quantified the mesoplastic (MEP, > 5.0 mm) and coarse microplastics (CMP, 2.0–5.0 mm) content of twelve floodplain soils. At four transects in the catchment area of the Lahn river (Germany), soils down to a depth of 2 m were examined for plastic content for the first time. MEP and CMP were detected through visual examination after sample preprocessing and ATR-FTIR analyses. Average MEP and CMP concentrations range between 2.06 kg −1 (±1.55 kg −1 ) and 1.88 kg −1 (±1.49 kg −1 ) with maximal values of 5.37 MEP kg −1 to 8.59 CMP kg −1 . Plastic particles are heterogeneously distributed in samples. Both plastic size classes occur more frequently in topsoils than in soil layers deeper than 30 cm. The maximal depth of CMP occurrence lies between 75 and 100 cm. Most common CMP polymer type was PE-LD, followed by PP and PA. MEP and CMP particles occur frequently at near channel sides and more often on riparian strips or grassland than on farmland. Vertical distribution of CMP indicates anthropogenic relocation in topsoils and additional deep displacement through natural processes like preferential flow paths or bioturbation. By comparing sedimentation rates of the river with the maximum age of plastic particles, sedimentation as a deposition process of plastic in floodplains becomes probable. From our findings, it can be concluded that an overall widespread but spatial heterogenous contamination occurs in floodplain soils. Additionally, a complex plastic source pattern seems to appear in floodplain areas. Graphical abstract: Image 1 Highlights: First examination of plastic contents in complete soil profiles up to 2 m depth. Higher occurrence of plastics in topsoils with heterogenous vertical distribution. Results indicate a complex source pattern for plastic particles in floodplains. Deep deposits of larger microplastics indicate vertical displacement processes. Abstract : Main findings: Mesoplastics and coarse microplastic in floodplain soils occur widespread in both lateral and vertical soil sections resulting from a complex source pattern and in situ vertical translocations.